Ethane Direct Dehydrogenation over Carbon Nanotubes and Reduced Graphene Oxide. Issue 34 (8th September 2021) - Bychko, Igor; Abakumov, Alexander; Nikolenko, Andrii; Selyshchev, O. V.; Zahn, D. R. T.; Khavrus, Vyacheslav O.; Tang, Jianguo; Strizhak, Peter
Abstract: The catalytic activity of multi‐walled carbon nanotubes (MWCNT) and reduced graphene oxide (rGO) in the ethane direct dehydrogenation reaction at temperatures up to 700 oC was studied. Obtained materials were characterized by transmission and scanning electron microscopy, X‐ray diffraction, Raman, and X‐ray photoelectron spectroscopies. The selectivity for ethylene of 80–90 % was achieved. The high stability of catalysts at 700 °C was demonstrated. It was shown that ethane and hydrogen are adsorbed on the same adsorption sites and hydrogen suppresses ethane dehydrogenation. Abstract : Direct ethane dehydrogenation: Multi‐walled carbon nanotubes and reduced graphene oxide was synthesized by conventional methods. Catalytic properties of obtained materials were shown in the ethane dehydrogenation. Ethane conversion of 20 % with an ethylene yield of 13 % can be achieved. High stability of catalysts at 700 °C demonstrated.